Quantifying the effect of pedestrian control devices on pedestrian safety - Baumanis, Carolina (2018)
There are many interventions that can reduce pedestrian crashes, including clarifying the indications transmitted to the travelers in the traffic network via the built environment. By design, the built environment aims to make who has the right-of-way very clear by presenting expected, easy-to-interpret indications. Some environments are much clearer than others, for example a marked crosswalk versus an unmarked crosswalk and can influence yielding behavior and fatal crash probability. This thesis presents the findings on driver yielding toward pedestrians at various crossing treatments and on fatal pedestrian crash incidents in the city of Austin, Texas. Considering both types of data, this thesis aims to achieve a well-rounded quantification of the effect pedestrian control devices have on overall pedestrian safety. From the result of the first component of the investigation, the effect of a flexpost island is not significantly different from the effect of a marked crosswalk on driver yielding propensity. Significant differences were observed between yielding at concrete refuge islands and every other pairwise comparison to flexpost islands, marked crosswalks, and unmarked crosswalks. From the second component, interaction seems to exist between treatment and both sidewalk presence and bus stop presence. The difference in fatality crashes at locations with and without pedestrian crossing treatments is less when there is no sidewalk present. Additionally, the difference between treatment presence on pedestrian fatality percentage is less when there is a bus stop more than 358 ft away. Civil, Architectural, and Environmental Engineering